Mechanism-Based Thinking on Policy Diffusion: A Review of Current Approaches in Political Science - Heinze, Torben (2011)
Abstract: Despite theoretical and methodological progress in what is now coined as the third generation of diffusion studies, explicitly dealing with the causal mechanisms underlying diffusion processes and comparatively analyzing them is only of recent date. As a matter of fact, diffusion research has ended up in a diverse and often unconnected array of theoretical assumptions relying both on rational as well as constructivist reasoning – a circumstance calling for more theoretical coherence and consistency. Against this backdrop, this paper reviews and streamlines diffusion literature in political science. Diffusion mechanisms largely cluster around two causal arguments determining the desires and preferences of actors for choosing alternative policies. First, existing diffusion mechanisms accounts can be grouped according to the rationality for policy adoption, this means that government behavior is based on the instrumental considerations of actors or on constructivist arguments like nor